Effectiveness of Domestic Wastewater Treatment Plant (WWTP) at Clinic Laboratory X (Case Study of Clinic Laboratory X in Pontianak City - Setiadi, Ade; Suswati, Denah; Diba, Farah (Universitas Tanjungpura, 2025)
This clinical laboratory plays a vital role in supporting the health sector by conducting tests and analyses related to diseases, health conditions, and factors affecting the community. However, these activities also generate domestic liquid waste that can pose a serious threat to the environment and public health if not managed effectively. Effective management of domestic liquid waste is crucial, given the importance of the clinical laboratory's role in supporting the health sector and the need for accurate testing.